Analisis Perlindungan Hukum terhadap Warna yang Diakui sebagai Merek Dagang dalam Hukum Internasional dan Hukum Nasional Indonesia - Joy Daniel Tarigan; Jelly Leviza; Fajar Khaify Rizky (CV Rewang Rencang, 2025)
Color protection as trademark faces harmonization challenges between international and national legal standards. The TRIPS Agreement recognizes color combinations with requirements of distinctiveness through secondary meaning and non-functionality, where developed countries like the United States and Australia even protect single colors as demonstrated in cases like Louboutin v. YSL. However, Indonesia through Law No. 20 of 2016 only recognizes